Museums, conversations, and learning (2014)
In this study, 178 groups of visitors were interviewed and recorded during their visits to museums. Three clusters of elements were shown to influence learning: the identity of the visitors, their response to the learning environment, andtheir explanatory engagement during the visit. A structural equation model using these variables fit well. Further examination revealed that not all conversational behavior was supportive of learning; some actions, such as making frequent personal connections, were detrimental to learning; additionally, silent contemplation was modestly associated with learning. This paper discusses these findings through the experiences of four couples whose outcome measures placed them at the extreme high or low end of the learningdistribution.